Analisis Pengendalian Internal dan Dompet Digital Terhadap Keberhasilan UMKM Mempawah dengan E-Marketing Sebagai Moderasi - Syarifah Najua Amira; Febriati Febriati; Ali Afif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine how internal control systems, digital wallets, and e-marketing affect the success of MSMEs in Mempawah Regency. A quantitative research method was used. The data was analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM). Data were obtained from 100 MSME respondents in Mempawah Regency through purposive sampling. The analysis results show that internal control systems influence the success of MSMEs. Likewise, digital wallets have been proven to influence the success of MSMEs. Conversely, e-marketing does not influence the success of MSMEs. In the meantime, the impact of internal control systems on MSMEs' success could be mitigated by e-marketing interactions. Likewise, e-marketing interaction was able to moderate The impact of digital wallets on the success of MSMEs. Therefore, it can be concluded that MSMEs' prosperity is significantly impacted by internal control systems and digital wallets, while the role of e-marketing is still less than optimal.